1996
DOI: 10.1086/192365
|View full text |Cite
|
Sign up to set email alerts
|

MG Emission from Hybrid-Chromosphere Stars: 1.5 Decades of Chromospheric Variability Monitoring

Abstract: We present an analysis of the available long-wavelength, high-dispersion spectra of seven hybridchromosphere stars obtained with the International Ultraviolet Explorer between 1978 and 1993. Our investigation of the variability of the Mg n h and k resonance doublet demonstrates that the emissionline fluxes are not rotationally modulated with the periods previously suggested by Brosius, Mullan, & Stencel. Furthermore, we find no evidence in the Mg n data to corroborate the multiple periodicities reported in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…stellar chromospheric studies. Typical spectroscopic diagnostic lines include Ca ii H and K, Mg ii h and k, and Ly (Brown et al 1996;Schrijver & Zwaan 2000), which our data unfortunately do not include. G227-5's spectrum ( Fig.…”
Section: Chromospheric Structurementioning
confidence: 91%
“…stellar chromospheric studies. Typical spectroscopic diagnostic lines include Ca ii H and K, Mg ii h and k, and Ly (Brown et al 1996;Schrijver & Zwaan 2000), which our data unfortunately do not include. G227-5's spectrum ( Fig.…”
Section: Chromospheric Structurementioning
confidence: 91%
“…Following the method given by Brown et al (1996), synthetic time series data was generated with the same sampling as the observed data and the frequencies were searched over the same range as done with the real data. The synthetic time series are built by using a random number generator with a Gaussian distribution of points…”
Section: Methods Bmentioning
confidence: 99%
“…Following the method given by Brown et al (1996), synthetic time‐series data were generated with the same sampling as the observed data and the frequencies were searched over the same range as done with the real data. The synthetic time series is built by using a random number generator with a Gaussian distribution of points where x represents the magnitude of the light curve, α= exp(−Δ t / L corr ), where Δ t is the time between magnitudes x i −1 and x i , β= (1 −α 2 ) 1/2 , and R (0, σ) is the random number generator with a dispersion σ, which is the variance of the time‐series data.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hybrid bright giants of slightly earlier spectral type show evidence of terminal velocities comparable to the escape speed V 1 =V esc $ 1. For example, Aqr (G2 Ib; Dupree et al 1992b) and TrA ( K3 II) have been observed infrequently to show such a high-velocity wind component in addition to the slower persistent wind flow ( Hartmann et al 1985;Brown et al 1996). The metal-deficient field giant HD 6833 (G9.5 III) also shows a fast wind ( Dupree et al 1992a).…”
Section: Singg Le Starsmentioning
confidence: 99%